Anger Management Program to Overcome Anger and Aggression: A Meta-Analysis Study - Nauraliefia, Dinda Nabila; Yudiarso, Ananta (Universitas Negeri Malang, 2023)
This research aims to investigate the effectiveness of an anger management program in reducing feelings of anger and aggression in individuals. The meta-analysis research method was used to see the effect size of anger management programs in 11 previous experimental studies, with a total of 501 participants with different demographic backgrounds. Effect size can be analyzed from the number of research participants (N), average score (mean), and standard deviation (SD) of each experimental and control group. The research results show a large effect size (Hedges' g equals -1.44; g greater than .8) and 95 percent CI equals -2.658 to -.219) from implementing the anger management program in reducing individual anger and aggression. There is publication bias (Egger's regression equal to -5.419; p less than or equal to .001), which is a weakness in this research, so that it can be a concern for future research.